2014
DOI: 10.1007/s13353-014-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between temperament and sexual precocity indicator traits in Nellore cattle

Abstract: The aim of this study was to estimate the genetic associations between temperament and sexual precocity indicators in Nellore cattle. Temperament was evaluated at approximately 550 days of age, using three traits: i) movement score (MOV), recording the animals' movement inside the crush; ii) temperament score (TS) for assessing the reactions of animals in a corral pen; and iii) flight speed test (FS), recording the speed (in m/s) at which the animals exit the crush after being weighed. Three sexual precocity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
11
0
3
Order By: Relevance
“…The definition of the HP trait in the current study was similar to that of Boligon & Albuquerque (2011), who reported heritability estimate equal to 0·5 ± 0·02 and concluded that it is advantageous to use HP in selection for sexual precocity in Nellore cattle. Valente et al (2015) estimated heritability equal to 0·4 ± 0·06 for the HP trait in Nellore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of the HP trait in the current study was similar to that of Boligon & Albuquerque (2011), who reported heritability estimate equal to 0·5 ± 0·02 and concluded that it is advantageous to use HP in selection for sexual precocity in Nellore cattle. Valente et al (2015) estimated heritability equal to 0·4 ± 0·06 for the HP trait in Nellore.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to standard weights and visual scores, two other factors have been considered for improving herd breeding performance: the assessment of sexual precocity and fertility (Guarini et al 2015), by evaluating traits such as age at first calving (AFC), heifer pregnancy (HP) and stayability (STAY; the probability of a cow to produce at least three calves before reaching 76 months of age). Anticipating the AFC is directly linked to the efficiency and profitability of beef cattle production although this reproductive trait has a low heritability (Buzanskas et al 2010; Valente et al 2015). Generally, reproductive traits have low heritability estimates, but high economic importance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cows' physiological state, other factors have also been implicated in the relationship between beef cattle temperament and reproductive performance, such as genetic factors (Phocas et al, 2006;Valente et al, 2014) and the quality of human-animal interactions (Dobson et al, 2001). For instance, in a study conducted with dairy cattle, the use of negative actions by stockpersons (e.g., slaps, pushes, hits, and tail twists) was negatively correlated with cows' conception rate (Hemsworth et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A NTe consistiu na classificação visual por observação do comportamento/reatividade do animal, de acordo com as características de perturbação dele, durante seu período de permanência no tronco de contenção. Essa avaliação foi aferida para todos os animais pelo mesmo avaliador, classificada de 1 a 5, com base nos trabalhos de Paranhos da Costa et al 2015e Valente et al (2015), modificada conforme descrito a seguir: NTe1 = sem comportamento de estresse = animal parado sem expressar incômodo durante atividade no brete (extremamente tranquilo, sem movimentos bruscos de cauda, orelhas e cabeça; permite total proximidade do observador sem alterar comportamento); NTe2 = comportamento de estresse baixo = animal calmo ou pouco ativo durante atividade no brete (pouca movimentação; animal tranquilo, mas alerta; parado na maior parte do tempo de observação; permite certa proximidade do observador); NTe3 = comportamento de estresse moderado = animal inquieto durante atividade no brete (movimentação frequente, mas pouco vigorosa; animal agitado com movimento corporal indicativo de incômodo durante maior parte do tempo de observação); NTe4 = comportamento de estresse considerável = movimentação intensa durante atividade no brete (movimento constante da cauda, constante tentativa de fuga; animal tenso, debate-se vigorosamente; não permite grande proximidade do observador); NTe5 = comportamento de estresse alto = animal muito estressado (perturbado), dificultando o serviço no brete (movimentação constante e muito vigorosa; animal pula, levantando os membros do piso, o que causa grande ruído. Tenta atacar o observador).…”
Section: Methodsunclassified
“…Diferentes parâmetros têm sido utilizados para avaliar subjetivamente o temperamento, os quais se baseiam no comportamento e/ou na demonstração de agressividade do animal (Cooke et al, 2011;Valente et al, 2015). Maior reatividade do animal determina maior custo de manejo por aumentar a demanda de funcionários, acrescentar tempo necessário para a execução do serviço, diminuir a segurança de trabalho, reduzir a vida útil do curral e, ainda, aumentar o nível de estresse dos animais em geral (Paranhos da Costa et al, 2015).…”
Section: Introductionunclassified